2018
DOI: 10.1016/j.redox.2017.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-140-5p aggravates doxorubicin-induced cardiotoxicity by promoting myocardial oxidative stress via targeting Nrf2 and Sirt2

Abstract: Clinical application of doxorubicin (DOX), an anthracycline antibiotic with potent anti- tumor effects, is limited because of its cardiotoxicity. However, its pathogenesis is still not entirely understood. The aim of this paper was to explore the mechanisms and new drug targets to treat DOX-induced cardiotoxicity. The in vitro model on H9C2 cells and the in vivo models on rats and mice were developed. The results showed that DOX markedly decreased H9C2 cell viability, increased the levels of CK, LDH, caused hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(165 citation statements)
references
References 47 publications
9
155
0
1
Order By: Relevance
“…Previous studies indicated that Nrf2 deficiency exacerbated DOX-induced cardiotoxicity, whereas Nrf2 activation figure (a, b), *P < 0.05 versus the corresponding normal saline (NS) group mice injected with negative control (NC) adeno-associated virus 9, # P < 0.05 versus DOX-treated mice injected with AAV9-NC. In figure (c, d), *P < 0.05 versus PBS group treated with control vehicle, # P < 0.05 versus DOXtreated H9C2 cells with irisin protection provided protection against cardiac dysfunction in response to DOX [7,45]. Here, we found that irisin treatment blocked DOX-induced Nrf2 downregulation and preserved its transcriptional activity, as confirmed by the increased HO-1 protein level and Nqo1, Gclc, Gclm mRNA level (Fig.…”
Section: Akt/gsk3β/fyn/nrf2 Signaling Was Responsible For Fndc5-mediasupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies indicated that Nrf2 deficiency exacerbated DOX-induced cardiotoxicity, whereas Nrf2 activation figure (a, b), *P < 0.05 versus the corresponding normal saline (NS) group mice injected with negative control (NC) adeno-associated virus 9, # P < 0.05 versus DOX-treated mice injected with AAV9-NC. In figure (c, d), *P < 0.05 versus PBS group treated with control vehicle, # P < 0.05 versus DOXtreated H9C2 cells with irisin protection provided protection against cardiac dysfunction in response to DOX [7,45]. Here, we found that irisin treatment blocked DOX-induced Nrf2 downregulation and preserved its transcriptional activity, as confirmed by the increased HO-1 protein level and Nqo1, Gclc, Gclm mRNA level (Fig.…”
Section: Akt/gsk3β/fyn/nrf2 Signaling Was Responsible For Fndc5-mediasupporting
confidence: 66%
“…Excessive ROS induces oxidative damage to biological macromolecules, including lipids, proteins and DNA, and disrupts cellular membrane integrity and function [6]. Moreover, DOX-evoked oxidative stress can directly elicit massive cardiomyocyte apoptosis via both extrinsic and intrinsic apoptotic pathways and cause severe cardiac dysfunction [7,8]. Previous studies also demonstrated that DOX could induce apoptosis via mechanisms that do not directly involve ROS production and oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%
“…miR-93 was able to regulate the oncogenic process in mammaries through regulation of its target gene NRF2 (16). MicroRNA-140-5p aggravated doxorubicin-induced cardiotoxicity by promoting myocardial oxidative stress by targeting Nrf2 and Sirt2 (17). Nevertheless, the biological role of miR-144-3p in modulating lung cancer drug resistance by targeting Nrf2 is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is one of the most common malignancies in China, and its mortality is only second to lung cancer and liver cancer (1). A vast majority of clinically diagnosed cases are in the intermediate and advanced stage due to the lack of early specific symptoms and tumor markers for early detection and diagnosis, which has led to the high mortality of gastric cancer (13). Therefore, searching for tumor markers for the early screening or diagnosis of gastric cancer, together with developing agents with high efficiency and low toxicity is of great importance (14).…”
Section: Discussionmentioning
confidence: 99%